Derm facts - Sams, Hunter H. (Hanley & Belfus, 2001)
A portable "peripheral brain" of dermatologic information for physicians. Data is presented in 27 tables, organized alphabetically by subject. In addition to providing overviews of specific diseases of the skin, hair, nails, mouth, and mucus membranes, the reference covers advocacy and support groups, allergies and sensitizers, diet and foods, surgery, therapy, skin problems associated with medications, and other topics. The author is a dermatologist at Vanderbilt U. Medical Center. No index.